2016
DOI: 10.1128/aac.01514-15
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of OXA-162 Carbapenemase- and DHA-1 AmpC Cephalosporinase-Producing Sequence Type 11 Klebsiella pneumoniae Causing Community-Onset Infection in Greece

Abstract: b OXA-48-like carbapenemases have only recently emerged in Europe. OXA-162 is a rare OXA-48 variant usually coexpressed with extended-spectrum ␤-lactamases. Here, we report the identification of the first OXA-162 carbapenemase-producing Klebsiella pneumoniae isolates, which coexpressed an AmpC cephalosporinase (DHA-1), retrieved from a patient in Greece. They belonged to a single sequence type (ST11) and caused the first documented community-onset urinary tract infections attributable to an OXA-48-like-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Since then, sporadic cases have been observed in hospitals in Athens (Attica), Patras (Peloponnese, western Greece) and Larissa (Thessaly, central Greece), all belonging to multilocus sequence type (ST) 11 type [4][5][6]. The first OXA-48-like carbapenemase outbreak was detected in 2012 [7] and apart from single cases [8,9], no major epidemics have been recorded in Greece.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, sporadic cases have been observed in hospitals in Athens (Attica), Patras (Peloponnese, western Greece) and Larissa (Thessaly, central Greece), all belonging to multilocus sequence type (ST) 11 type [4][5][6]. The first OXA-48-like carbapenemase outbreak was detected in 2012 [7] and apart from single cases [8,9], no major epidemics have been recorded in Greece.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugatable bla OXA-48 (9/11) was the most prevalent carbapenemase detected in CPE from a hospital in Morocco collected in June to August 2011 [Barguigua 2015]. The first documented instance of a community acquired UTI due to an bla OXA-48-like producing Enterobacteriaceae was in Greece in January 2010 when a recovered K. pneumoniae ST11 isolate was found with carbapenem resistance due to bla OXA-162 [Voulgari 2015]. Multiple studies identified bla OXA-48 as the most prevalent carbapenemase in Spain, and this is associated with successful spread of K. pneumoniae , particularly ST11 [Branas 2015, Oteo 2015].…”
Section: Oxa-48-like Family Membersmentioning
confidence: 99%
“…6, 7.6, 7.4 and 5.4. PCR with specific primers and conditions [2,3] and sequencing of PCR products, confirmed the presence of bla CTX-M-15 , bla SHV-11 , bla OXA-48 and bla-TEM-1 , respectively. Multiplex PCR for 16S rRNA methylase genes revealed the carriage of armA gene in the K. pneumoniae isolate [3].…”
mentioning
confidence: 85%
“…web.pasteur.fr/klebsiella/klebsiella.html) assigning the isolate to Sequence type ST147. In Greece, OXA-48 and its variant OXA-162 carbapenemases were first detected in 2010 and were acquired by an ST11 K. pneumoniae clone [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation